1970
DOI: 10.1002/art.1780130611
|View full text |Cite
|
Sign up to set email alerts
|

Gold nephropathy a clinical and pathologic study

Abstract: Proteinuria developed in 5 of 75 rheumatoid arthritis patients treated with gold salts. In 2 of these 5 patients criteria for the nephrotic syndrome were fulfilled. Two other cases of gold‐induced nephrotic syndrome are also reported. Blood and urine gold levels were measured on 27 of the 75 patients and no difference was found between the 2 patients who eventually developed the nephrotic syndrome and the 25 who did not. Light, electronmicroscopic and histochemical studies revealed no difference in the site or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

1972
1972
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(30 citation statements)
references
References 22 publications
(22 reference statements)
0
29
0
1
Order By: Relevance
“…Gold salts, including oral and parenteral preparations, have been used in the treatment of RA for more than three quarters of a century, but recently, they have been largely replaced by safer, more efficacious agents. The most common side effect of gold is proteinuria, which develops in 3%-7% of patients (106,107). Renal biopsy most commonly reveals stage 1 or 2 MN, indicating early detection because of screening.…”
Section: Drugs Associated With Mnmentioning
confidence: 99%
“…Gold salts, including oral and parenteral preparations, have been used in the treatment of RA for more than three quarters of a century, but recently, they have been largely replaced by safer, more efficacious agents. The most common side effect of gold is proteinuria, which develops in 3%-7% of patients (106,107). Renal biopsy most commonly reveals stage 1 or 2 MN, indicating early detection because of screening.…”
Section: Drugs Associated With Mnmentioning
confidence: 99%
“…The incidence of proteinuria observed during gold treatment has varied between 1 and 10% [1][2][3][4][5][6] with occa sional reports of more than 20% [7], Proteinuria occurs in patients of both sexes, at all ages (2-73 years) and in association with all parenteral soluble gold preparations (thiomalate, thiosulphate, thioglucose, phenylphosphinic acid) [8,9] and with oral gold treatment (auranofin) [5], Proteinuria Although proteinuria may develop at any time from 2 weeks (10 mg) to more than 6 years (6,000 mg) during treatment [6,[10][11][12], in some 50% of patients the onset occurs in the first 6 months of treatment, in 70% by 12 months and in 85% by 24 months with a peak incidence (40%) in the second 3 months of treatment [13]. The severity and duration of the proteinuria vary greatly [8,13] and are not related to the total dose of gold received, the duration of treatment, the peak or mean serum gold levels or the urinary gold excretion [6,14].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Membranous glomerulonephropathy (MGN) usually occurs in rheumatoid arthritis patients treated with gold and penicillamine [16][17][18][19]. However, there have been a few cases of MGN in rheumatoid patients who had not received gold or penicillamine therapy; 2 of 8 patients reported by Samuel et al [20] and 1 of 2 patients reported by Row et al [21], Patients with RA and asymptomatic hematuria may have some mesangial changes (increase in mesangial matrix and/or mesangial cells and electron-dense deposits) [16] which are similar to those of patients with isolated hematuria [22], Another commonly reported histologic abnormality is tubulointerstitial disease [16].…”
Section: Dr Akmalmentioning
confidence: 99%
“…The immunologic nature of the glomerular lesions is supported by serologic studies of a patient receiving gold therapy who had circulating immune complexes and antibodies to a variety of tissue antigens concomi tant with the development of the nephrotic syndrome [34]. Furthermore, the low incidence of symptomatology coupled with the finding of gold deposits in the kidneys of some patients without proteinuria argues for a hyper sensitivity reaction to gold in these patients [18]. The nephrotic syndrome of our patient does not seem to be due to gold therapy, since this treatment was discontin ued 6 weeks before the appearance of the nephrotic syn drome and the patient did not have proteinuria during and immediately after gold therapy.…”
Section: Dr Akmalmentioning
confidence: 99%